2019
DOI: 10.1352/1934-9556-57.1.66
|View full text |Cite
|
Sign up to set email alerts
|

In Their Own Words: Perceptions and Experiences of Bullying Among Individuals With Intellectual and Developmental Disabilities

Abstract: Despite the high incidence of bullying among people with intellectual and developmental disabilities (IDD), little research has been conducted with people with IDD as participants reporting their own perceptions and experiences of bullying. To address this shortcoming, we interviewed 18 adults with IDD regarding these issues. Four major themes emerged from our qualitative analysis of the transcribed interviews: (a) bullying is hurtful, (b) why people bully, (c) bullying takes many forms, and (d) bullying can h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Factors including age, types of caregiving, psychotropic use, and psychiatric symptoms were associated with PV experience in the present study (data were not shown). Research has shown similarly that being alone, being younger, being physically weaker, having secondary disabilities, and having a more severe disability would make victimization more likely [ 18 ]. Individuals with ID who experienced victimizationrelated emotional problems, low self-esteem, and a negative social impact [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors including age, types of caregiving, psychotropic use, and psychiatric symptoms were associated with PV experience in the present study (data were not shown). Research has shown similarly that being alone, being younger, being physically weaker, having secondary disabilities, and having a more severe disability would make victimization more likely [ 18 ]. Individuals with ID who experienced victimizationrelated emotional problems, low self-esteem, and a negative social impact [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of victimization is high among those with ID; the types of victimization include assault, exclusionary behavior, threats, verbal bullying, and sexual harassment [ 15 , 16 , 17 ]. Victimization is most frequently reported in school, group home, supported employment, family home, and community settings [ 18 ]. Studies have also revealed that victimization experiences are associated with poor mental health among individuals with ID [ 15 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A final set of limitations relates to the lack demographic information about participants. As explained in a related study based on the same set of interviews (Griffin et al, ), we did not collect demographic information aside from age and gender. In interviews, participants provided examples of bullying and other victimization, including accounts of abuse and assault; this type of data requires careful protection of identifying information.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were not asked to report on bullying experiences within a specific time frame; rather, questions were intentionally left without a specific time frame to allow the research team to gather richer details on their most salient bullying experiences (e.g., see Fisher, Moskowitz, & Hodapp, ) and to allow for restrospective reflection of the impact of bullying on their lives. A prior study (Griffin, Fisher, Lane, & Morin, ) focused on characterizing participants' experiences of bullying and recommendations for prevention, whereas the current study focuses on participants' responses to bullying. Interviews were recorded, transcribed and uploaded to a qualitative data analysis program.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the decline in the institutionalisation of people with ID, an unfortunate legacy of social isolation remains. People with ID commonly report being targets of verbal and even physical abuse (Griffin et al 2019), alongside other more subtle acts of stigma such as feeling unwelcome when out in public, using public transportation or at work (McEvoy and Keenan 2014). Moreover, public opposition has prevented the opening of community facilitiessuch as group homesfor people with ID (Van Alphen et al 2012).…”
Section: Introductionmentioning
confidence: 99%